The Male/Female Students’ Attitudes in the University College to Applied Sciences in Gaza Towards Learning Arabic Grammar Remotely in the Course of Arabic Language Requirement During Corona Pandemic (Journal of the College of Education for Women, 2022)
This study deals with examining UCAS students’ attitudes in Gaza towards learning Arabic grammar online during the Corona pandemic. The researcher has adopted a descriptive approach and used a questionnaire as a tool for data collection. The results of the study have statistically shown significant differences at the level of "0.01" between the average scores of students in favor of the students of the humanities specializations. It has also been found that the students’ attitudes at the Department of Humanities and Media towards learning Arabic grammar online are positive. Additionally, the results revealed no statistical significant differences due to the variable of UCAS students’ scientific qualifications. The results stressed that university students urgently need to learn Arabic grammar to avoid mistakes during their speeches, and to improve their writings. The study has finally presented as a conclusion a set of recommendations related to the importance of teaching Arabic grammar in the university colleges, academic institutions, and in the different stages of education. It has further enhanced confidence in learning the Arabic grammar, and having pride in it. Such a conclusion helps preserve the Noble Qur’an and the Arabic language and its entity, work to spread it by all available means, pay attention to Arabic grammar, teach it and learn it, work to disseminate it by all available means, and support all efforts made in this direction locally, Arab and Islamic.